3D visualisation [ - Eden, Bradford Lee (Bradford, England : Emerald, 2007)
This special issue of 'Library Hi Tech' presents some interesting and fascinating ways in which libraries and librarians are currently exploring multidimensional ways of presenting information. Six articles explore current developments and applications in 2D and 3D information visualization, which will hopefully encourage other libraries and librarians to begin discussions and experiments in meeting the needs of our users, who are already well ahead of us in this arena
1. Cover; CONTENTS; EDITORIAL ADVISORY BOARD -- 2. Editorial; Holistic sense-making: conflicting opinions, creative ideas, and collective intelligence -- 3. Atale of binary bricks and mortar: building a virtual library -- 4. Human perception and knowledge organization: visual imagery -- 5. User interfaces for mobile navigation -- 6. Information visualization and large-scale repositories -- 7. Multimedia visualization and interactive systems -- 8. School library web site terminology -- 9. Paradigms shifts in information environment: prospects and challenges African libraries -- 10. The strategic evaluation of academic libraries
Title from PDF caption (viewed Nov 27, 2007)
Includes bibliographical references
Keywords: Library science -- Technological innovations